2015
DOI: 10.1007/s00259-015-3111-9
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest repeatability of myocardial blood flow and infarct size using 11C-acetate micro-PET imaging in mice

Abstract: (11)C-Acetate micro-PET assessment of iMBF and infarct size is repeatable and suitable for serial investigation of coronary artery disease progression and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Chemokine Receptor Type-2 C-C chemokine receptor type 2 (CCR2) is another important inflammatory cell marker involved in monocyte/macrophage recruitment, which has been evaluated for imaging myocardial inflammation using PET. In an ischaemia-reperfusion heterotopic heart transplantation mouse model, the PET tracer 64 Cu-DOTA-ECL1i was shown to bind CCR2 + monocytes and macrophages within donor hearts, demonstrating increased tracer uptake compared to native hearts [43]. Specific autoradiographic binding was also confirmed in human myocardial specimens.…”
Section: Tracers For Imaging Post-infarct Inflammationmentioning
confidence: 78%
See 2 more Smart Citations
“…Chemokine Receptor Type-2 C-C chemokine receptor type 2 (CCR2) is another important inflammatory cell marker involved in monocyte/macrophage recruitment, which has been evaluated for imaging myocardial inflammation using PET. In an ischaemia-reperfusion heterotopic heart transplantation mouse model, the PET tracer 64 Cu-DOTA-ECL1i was shown to bind CCR2 + monocytes and macrophages within donor hearts, demonstrating increased tracer uptake compared to native hearts [43]. Specific autoradiographic binding was also confirmed in human myocardial specimens.…”
Section: Tracers For Imaging Post-infarct Inflammationmentioning
confidence: 78%
“…Macrophage Phagocytosis 64 Cu-Macrin is a 20-nm spherical dextran nanoparticle tracer designed specifically to target macrophages. In a preclinical study, 64 Cu-Macrin was shown to report on the accumulation of macrophages within the infarcted myocardium in experiments using mice, rabbits and pigs [45•].…”
Section: Tracers For Imaging Post-infarct Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the usage of 99mTc-sestamibi and 13N-ammonia PET showed a valid assessment of cardiac function in healthy and infarct mice compared to MRI and contrast CT ( 28 ). Furthermore, Croteau et al depicted a robust test and retest repeatability for mouse infarct assessment by using 11C-acetate micro-PET imaging ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in the study by Hess et al, heart rate of mice was in the physiological range (on average 477 beatsÁminute -1 ) as recommended in the guidelines. 1 Nuclear imaging in small animal models of ischemic heart disease is appealing, because it enables accurate measurement of MI size, 5-9 evaluation of myocardial perfusion, 10,11 and molecular imaging of metabolism such as oxygen consumption combined with substrate metabolism. 12,13 However, previous studies evaluating nuclear imaging for the assessment of cardiac volumes and function have been mainly focused on other conditions than MI.…”
Section: See Related Article Pp 1317-1327mentioning
confidence: 99%